Extraordinary high-Q resonances in the scattering by a dielectric slab containing a grating of circular cylinders - Byelobrov, V.O.; Benson, T.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
An infinite dielectric wire grating in free space is known to possess very high-Q
resonances at the frequencies close to the Rayleigh anomalies. Still a practical
implementation of such a resonator may require its embedding in a dielectric slab. In this
paper, it is shown that this can bring additional improvement of the Q-factors. A
dielectric slab with a symmetrically embedded dielectric-wire grating is investigated
under the normal incidence of plane waves. Accurate numerical solutions are derived for
the E- and H-polarization cases. Associated eigenvalue problems are solved for the realvalued
lasing frequencies and the threshold values of material gain.